The Influence of Service Quality, Brand Image, and Price on Customer Satisfaction of Hardware at Palembang Icon - Nainggolan, Angelina Lydia; Pramuditha, Charisma Ayu (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze both partially and simultaneously the influence of service quality, brand image, and price on customer satisfaction at Hardware Palembang Icon. The research sample consisted of 372 respondents using a Likert scale questionnaire. The study employed a quantitative approach with purposive sampling technique. The results indicate that service quality, brand image, and price have a significant effect on customer satisfaction at Hardware Palembang Icon, both partially and simultaneously.